Some (criminal) procedural problems of the parliamentary inquiry: parliamentary review of the jurisdictional function, information flows and practical concordance. (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2023)
Parliamentary investigations are admissible when they relate to the same facts that are being investigated or prosecuted by the criminal courts. However, a parliamentary enquiry aimed exclusively at declaring the existence or non-existence of criminal or administrative offences is not constitutionally acceptable. On the other hand, the simultaneousness of activities raises difficulties with regard to the independence (particularly if the parliamentary enquiry concerns jurisdictional activity) and impartiality of judges and magistrates, especially if they are lay judges. Simultaneity is also problematic with regard to the cooperation obligations of the Committees of inquiry (CI) and the Tribunals. Neither of the two organs is exempt from cooperating (even when their activity is secret), as long as the recipient of the documentation (for example) can maintain the same level of secrecy. On the other hand, when the investigation is parallel and a summoned person is in pre-trial detention, the Court has no power to refuse the presence of the summoned person before the CI. Finally, the simultaneity of investigations requires the guarantee of the so-called "practical concordance", which translates into the obligation of judges and magistrates to collaborate (positively) with the parliamentary investigation and to abstain (negatively) from influencing it; in the obligation of the CI to collaborate with the judicial authorities and to respect the judicial activity; and in the obligation of the CI to cooperate with the judicial authorities and to respect the judicial activity.
Keywords: Parliamentary committees of inquiry; criminal proceedings; procedural guarantees; simultaneity; secrecy